Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/hep.21440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disease severity on outcome of antiviral therapy for chronic hepatitis C: Lessons from the HALT-C trial

Abstract: In patients with chronic hepatitis C, advanced fibrosis and cirrhosis are associated with lower rates of sustained virologic response (SVR) to interferon (IFN)-based therapy. In this study, we assessed virologic response to retreatment with peginterferon alfa-2a and ribavirin (RBV), as a function of the baseline fibrosis score (Ishak staging) and platelet count, in 1,046 patients enrolled in the Hepatitis C Antiviral Long-term Treatment against Cirrhosis (HALT-C) Trial. All patients had failed prior treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 26 publications
10
112
1
2
Order By: Relevance
“…This is in variance with studies performed in CHC (27)(28)(29). In contrast, studies in CHB have reported both favorable (16) and unfavorable results (30 However, clinically important adverse events occurred in patients with advanced liver disease, which included two cases of hepatic decompensation and one case of tuberculosis reactivation.…”
Section: Discussionmentioning
confidence: 80%
“…This is in variance with studies performed in CHC (27)(28)(29). In contrast, studies in CHB have reported both favorable (16) and unfavorable results (30 However, clinically important adverse events occurred in patients with advanced liver disease, which included two cases of hepatic decompensation and one case of tuberculosis reactivation.…”
Section: Discussionmentioning
confidence: 80%
“…The National Institutes of Health (NIH)-sponsored Hepatitis C Antiviral Long-Term Treatment aganist Cirrhosis (HALT-C) clinical trial failed to show a benefit of maintenance interferon on differences in the rates of mortality, decompensation, HCC, or fibrosis progression between the peginterferon alpha-2a maintenance group and the control group [220]. A similar study in HIVpositive individuals -the SLAM-C study -was also unable to show any beneficial effect on fibrosis progression rates [221].…”
Section: Nonresponders and Relapsersmentioning
confidence: 99%
“…Thus, theoretically, patients with a high fraction of HCV-infected hepatocytes will have high ε c and hence will have a poorer chance of achieving SVR. Interestingly, Pal et al [47] showed that advanced liver disease is associated with a higher fraction of HCV-infected hepatocytes and lower SVR rates (<29%) than for patients without liver disease [25,26,48,49].…”
Section: Critical Drug Efficacymentioning
confidence: 99%